It's common to know the triple angle formula, tan(3x)=tan(x)⋅tan(x−3π)⋅tan(x+3π). David Vreken pointed out in his unworldy solution here that quintuple angle formula below also holds! tan(5x)=tan(52π−x)tan(5π−x)tan(x)tan(5π+x)tan(52π+x). He even suggested that the following generalization must be true as well for any positive integer n. Can anyone prove it? tan[(2n+1)x]=(−1)nk=1∏2n+1tan(x+2n+1k−n−1π)
#Geometry
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
We have the identities sinnx=2n−1k=0∏n−1sin(x+nkπ) and cosnx=2n−1k=1∏nsin(x+2n(2k−1)π). If you divide these, you should be able to manipulate the quotient to get what you want.
References:
https://mathworld.wolfram.com/Multiple-AngleFormulas.html
https://math.stackexchange.com/questions/2095330/product-identity-multiple-angle-or-sinnx-2n-1-prod-k-0n-1-sin-left
Summoning @Mark Hennings
I found the tan5x equation here. There seems to be a start of a proof for it but I don't understand it. Perhaps someone can figure that out and generalize it.
Here's a start to a proof:
Since tanx=i(eix+e−ix)eix−e−ix=i(e2ix+1)e2ix−1, that means that tan(x+a)=i(e2ixe2ia+1)e2ixe2ia−1. Therefore,
tan(3π−x)⋅tanx⋅tan(3π+x)
=−tan(x−3π)⋅tanx⋅tan(x+3π)
=−i(e2ixe−32πi+1)e2ixe−32πi−1⋅i(e2ix+1)e2ix−1⋅i(e2ixe32πi+1)e2ixe32πi−1
=−i3(e6ix+e4ix(e32πi+e−32πi+1)+e2ix(e32πi+e−32πi+1)+1)e6ix−e4ix(e32πi+e−32πi+1)+e2ix(e32πi+e−32πi+1)−1
=i(e6ix+e4ix(0)+e2ix(0)+1)e6ix−e4ix(0)+e2ix(0)−1
=i(e6ix+1)e6ix−1
=tan3x
Likewise,
tan(52π−x)⋅tan(5π−x)⋅tanx⋅tan(5π+x)⋅tan(52π+x)
=tan(x−52π)⋅tan(x−5π)⋅tanx⋅tan(x+5π)⋅tan(x+52π)
=i(e2ixe−54πi+1)e2ixe−54πi−1⋅i(e2ixe−52πi+1)e2ixe−52πi−1⋅i(e2ix+1)e2ix−1⋅i(e2ixe52πi+1)e2ixe52πi−1⋅i(e2ixe54πi+1)e2ixe54πi−1
=i5(e10ix+e8ix(e54πi+e−54πi+e52πi+e−52πi+1)+e6ix(e56πi+e−56πi+e54πi+e−54πi+2e52πi+2e−52πi+2)+e4ix(e56πi+e−56πi+e54πi+e−54πi+2e52πi+2e−52πi+2)+e2ix(e54πi+e−54πi+e52πi+e−52πi+1)+1)e10ix−e8ix(e54πi+e−54πi+e52πi+e−52πi+1)+e6ix(e56πi+e−56πi+e54πi+e−54πi+2e52πi+2e−52πi+2)−e4ix(e56πi+e−56πi+e54πi+e−54πi+2e52πi+2e−52πi+2)+e2ix(e54πi+e−54πi+e52πi+e−52πi+1)−1
=i(e10ix+e8ix(e54πi+e−54πi+e52πi+e−52πi+1)+2e6ix(e54πi+e−54πi+e52πi+e−52πi+1)+2e4ix(e54πi+e−54πi+e52πi+e−52πi+1)+e2ix(e54πi+e−54πi+e52πi+e−52πi+1)+1)e10ix−e8ix(e54πi+e−54πi+e52πi+e−52πi+1)+2e6ix(e54πi+e−54πi+e52πi+e−52πi+1)−2e4ix(e54πi+e−54πi+e52πi+e−52πi+1)+e2ix(e54πi+e−54πi+e52πi+e−52πi+1)−1
=i(e10ix+e8ix(0)+2e6ix(0)+2e4ix(0)+e2ix(0)+1)e10ix−e8ix(0)+2e6ix(0)−2e4ix(0)+e2ix(0)−1
=i(e10ix+1)e10ix−1
=tan5x
Since e2n+1−2nπi+e2n+1−2(n−1)πi+...+e2n+1−2πi+e2n+10πi+e2n+12πi+...+en+12(n−1)πi+e2n+12nπi=0 for any integer n, the above middle terms will always cancel out for the general case (more work needed here) and will prove the given generalization.